Commissioning healthcare in England : evidence, policy and pactice / edited by Pauline Allen [and three others]. - Allen, Pauline (Professor of health services organisation) (Policy Press, 2020)
This timely book is the most comprehensive account yet of recent commissioning practice in the English NHS and its impact on health services and the healthcare system. Drawing on eight years of research, expert researchers in the field analyse crucial aspects of commissioning, including competition and cooperation, the development of Clinical Commissioning Groups and contractual mechanisms. They also consider the influence of recent commissioning reforms on public health infrastructure. For academics and policy makers in health services research and policy, this is a valuable collection of evidence that deepens understanding of how commissioning works.